The Effect Of Economic Literature, Education, and Family Environment On Students' Consumption Patterns - Tri Mega Nur Utami; Kusuma Chandra Kirana; Jajuk Herawati (Green Publisher Indonesia, 2021)
This study aims to describe the effect of economic literacy, education, and family environment on consumption patterns. The method used is the quantitative method with variable in research is economic literacy (X1), education (X2), and family environment (X3) on consumption patterns (Y). Population in this study were 100 FE students. Online questionnaire survey and the sampling technique used is probability sampling used to collect data. The data analysis technique used is multiple linear regression analysis. The results showed that (1) Economic literacy had a positive but not significant effect on consumption patterns, (2) Education had a positive and significant effect on consumption patterns, (3)Family environment had a positive and significant effect on consumption patterns.